THE EFFECT OF FINANCIAL LITERACY ON STUDENT FINANCIAL BEHAVIOR (Case Study of Students of Faculty of Economic, University of Dehasen Bengkulu) - Afriani, Sulisti; Yanti, Rina Trisna (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
Abstract : Financial literacy is very important for everyone to know, the higher a person's financial literacy level, the better his financial behavior will be. This study aims to analyze the effect of financial literacy on student financial behavior in the Faculty of Economics, University of Dehasen Bengkulu. The sample used in this study was 100 students with a data questionnaire method. The results show that the regression model of the regression equation is as follows: Y = 12.519 + 0.745X, the correlation coefficient r = 0. lies between 0.600 - 0.799 including in a strong correlation, R Square of 0.556 means that the variable student financial behavior can be influenced by the variable Financial literacy of 55.6%. While the remaining 44.4% is influenced by other variables not examined in this study. . Because the value of α